An FTIR emission study of the products of NO A2Σ+ (v = 0, 1) + O2 collisions. Issue 18 (18th April 2017) - Few, Julian; Fletcher, James D.; Hancock, Gus; Redmond, Jennifer L.; Ritchie, Grant A. D.
Abstract : Products of the quenching of NO A 2 Σ + ( v = 0, 1) by O2 are observed by time-resolved FTIR emission. Vibrationally excited ground electronic states of NO and NO2 are seen, and reactive channels are identified. Abstract : Collisional quenching of NO A 2 Σ + ( v = 0, 1) by O2 has been studied through the detection of vibrationally excited products by time-resolved Fourier transform infrared emission spectroscopy. Non-reactive quenching of NO A 2 Σ + ( v = 0) produces a vibrational distribution in NO X 2 Π which has been quantified for v = 2–22, and is found to be bimodal. The results are consistent with two quenching channels. The first forms the ground X 3 Σ−g or low-lying a 1 Δg electronic state of O2 with a distribution including high vibrational levels of NO X 2 Π which is slightly hotter than statistical. Two possibilities are identified for the second channel. The first, with a similar quantum yield to that producing higher vibrational levels, forms a highly electronically excited state, such as O2 c 1 Σ−u, with low vibrational levels in NO X 2 Π which are inverted with a distribution resembling that resulting from a sudden or harpoon mechanism. The second is that ground state oxygen is formed with low vibrational energy partitioned into NO X 2 Π. In addition, vibrationally excited NO2 is observed, but at intensities which indicate that it is formed in low quantum yield. Quantitatively unobservable processes (defined as those which do not form ground state NO ( v ≥ 2)) are found to have a branching ratio of at most 25 ± 5%. The results are compared with those of previous studies and the most consistent interpretation suggests that dissociation of O2 to form ground state O( 3 P) atoms and ground vibrational state NO X 2 Π ( v = 0) is the main reactive process rather than NO2 formation. Qualitatively similar results are seen for the quenching of NO A 2 Σ + ( v = 1).